Formulation development of a biphasic release tablet-in-tablet system containing ketorolac tromethamine - Ping Zou; Yuan Zeng; Xiang-ru Liao; Xiang-yang Xie; Yin-ke Li; Yi-hui Ma; Hui Liu (PLoS ONE, 2026)
Ketorolac tromethamine (KT) is a potent nonsteroidal anti-inflammatory drug (NSAID) used for moderate to severe pain management. Its short elimination half-life necessitates frequent dosing, which can reduce patient compliance. The objective of this study was to formulate, develop, and optimize a novel biphasic-release tablet-in-tablet (TIT) system for KT to provide immediate pain relief followed by extended drug release. A TIT system was designed, comprising an immediate-release (IR) outer layer and an extended-release (ER) core matrix. The ER core was optimized using a 3 2 full factorial design, with the amounts of HPMC K100M and HPMC K4M as independent variables. Formulations were evaluated for pre- and post-compression parameters, drug-excipient compatibility, and in vitro drug release. The drug release kinetics and mechanism were analyzed using various mathematical models. The optimal ER core formulation (F1) exhibited a drug release of 4.6% at 0.5 h and 66.1% at 12 h, closely matching the theoretical profile (similarity factor f 2 = 51). Release kinetics followed the first-order model and the Korsmeyer-Peppas model indicated an anomalous (non-Fickian) release mechanism (n = 0.831). The corresponding TIT formulation (F11) demonstrated desired physicochemical properties: hardness of 75 N, friability of 0.59%, and rapid outer layer disintegration (<50 s). The TIT provided an initial burst release (~30%) within 30 minutes, followed by sustained release exceeding 90% over 24 hours. This TIT system represents a promising alternative to conventional KT tablets for effective pain management.